Students' perceptions on the implementation of recorded oral presentation / Kamilah Zainuddin and Che' Fadhilah Che' Lah - Zainuddin, Kamilah; Che' Lah, Che' Fadhilah (Universiti Teknologi MARA, 2022)
Nowadays, lecturers are integrating numerous technologies in their classrooms due to the Covid-19 outbreak. Hence, it has allowed the widespread use of recorded videos in English classrooms. Thus, this study has been conducted to find out the students' perceptions on the implementation of oral presentation through recorded video. 164 semester 1 Diploma students of Politeknik Kota Bharu were selected as respondents. The questionnaires were devised to collect data and tested for reliability with the result of Cronbach's Alpha=0.896. The findings show the Recorded Oral Presentation helps to increase students' confidence and eventually improves their speaking skills.